Surf Zone Mapping Using Multirotor Unmanned Aerial Vehicle Imagery. (30th May 2019) - Che Mat, Norhalim; Tahar, Khairul Nizam
Abstract : Surf zone is a sand area that stretches inside a breaking wave to limit the rise and fall of waves on the beach. Advanced technology in the geomatics field offers a fast and accurate solution to produce surf zone maps. The demand for surf zone map is increasing during the monsoon season, especially at coastal areas. Nowadays, the Unmanned Aerial Vehicle (UAV) or drone has become popular platform in the geospatial and surveying field. The aim of this study is to produce surf zone 3D surface mapping by using a multirotor Unmanned Aerial Vehicle. There are four phases in this study which are image acquisition, UAV image processing, photogrammetric results, and analysis. The image acquisition was solely obtained using a multirotor UAV based on the photogrammetric concept. The acquired UAV images were processed using commercial software with a specific workflow. Photogrammetric products such as digital elevation model, orthophoto, contour, and surf map zone were produced. The analyses of these results were conducted based on different epochs on the selected months. The accuracy for northing, easting, and height coordinates was 1.026m, 0.838m, and 0.419m, respectively. It can be concluded that the UAV was able to produce a surf zone map with reliable accuracy. This platform is very useful for fast decision making, especially during disaster incidents.